IMPROVING STUDENTS’ PRONUNCIATION ABILITY USING ENGLISH SONGS AT THE ELEVENTH GRADE OF SMAN 10 JENEPONTO - Muhmalia, Resky Ananda; Atmowardoyo, Haryanto; Sakkir, Geminastiti (State University of Makassar, 2024)
The purpose of this research was to ascertain how students in SMAN 10 Jeneponto's eleventh grade may improve their pronunciation ability by employing English songs. This research used a pre-experimental design and a quantitative methodology. The eleventh grade students of SMAN 10 Jeneponto comprise the population of this research, while the sample consisted of 33 students in class XI.3. Data were gathered using pre- and post-testing. The analysis's findings indicate that the post-test mean score was 72.96 in the